Hyperthermia (42°C) as an Adjuvant to Radiotherapy and Chemotherapy in the Treatment of the Allogeneic VX2 Carcinoma in the Rabbit - Muckle, D. S. (Nature Publishing Group, 1973)
As assessed by decrease in tumour volume and inhibition of tumour cell respiration and glycolysis, hyperthermia (intra-tumour temperature 42°C for one hour) potentiated the destructive effect of radiotherapy (1000 rad) on the allogeneic VX2 carcinoma in the hind limb of rabbits, and chemotherapy (methotrexate) produced a similar potentiation of irradiation. The resulting regression of the primary tumour in each case after dual therapy was comparable to that occurring after 3 applications of local hyperthermia, which has been shown to cure 50% of animals with this carcinoma. Combination therapy did not increase the survival time of the rabbits, however, all of which had lung and lymph node metastases at autopsy. The results focus attention on the relationship between a primary tumour and its metastases. The histological picture and the animal survival data suggest that the mechanism of tumour cell death and resorption of necrotic material following treatment may be important in enabling the host to deal with metastatic cells. After combination therapy, many metabolically and mitotically active cancer cells remained in the tumour mass, and the incomplete destruction of the primary tumour may have left the host with a burden of tumour cells too large to be destroyed by the immune system.